Key to Common Bay Trees of Florida - Lynn Proenza; Michael Andreu (EDIS, 2013)
Bay trees in Florida can be difficult to distinguish because their leaves all look alike at first glance. The leaves of bays are all simple, large, elliptical, and evergreen. In addition, several bay species grow in overlapping ranges and habitats. Many times, two or more different species of bay will be found growing right next to one other. This 7-page fact sheet includes a dichotomous key to help in the identification of common bay trees found in Florida. A basic description and photos of each species help with the identification process. Written by Lynn Proenza and Michael Andreu and published by the UF Department of School of Forest Resources and Conservation, September 2013.